Probing Silica—Organic Hybrid Materials Using Small Probes: Simulation of Adsorption Equilibria Influenced by Cooperativity Effects - Anton Panteleimonov; Oleg Tkachenko; Andrey Baraban; Edilson V. Benvenutti; Yoshitaka Gushikem; Yuriy Kholin (Adsorption Science & Technology)
The property of non-ideality (cooperativity effects, energetic heterogeneity of binding centres) is often observed at probing surfaces by small ionic or molecular probes. A procedure based on the model of polydentate binding is recommended as a tool for detection and quantitative characterization of these effects. This procedure allows one to find objective estimations of effective sorption capacities and constants of adsorption equilibria. In this study, adsorption of small probes by two hybrid silica–organic materials has been studied. Ormosil with immobilized n-propylamine was probed with H + ions, and in addition, CoCl 2 adsorption from solutions of ethanol by silica chemically modified with 3-n-propyltrimethoxysilane-1-methylimidazolium chloride was also investigated. In both cases, the model of bidentate binding properly fitted the experimental data. This made it possible to determine the quantitative characteristics of adsorption equilibria and to arrive at conclusions on the cooperativity effects. Negative cooperativity effects are significant in adsorption of H + ions, while strong positive cooperativity affects CoCl 2 binding.